Apremilast, an oral phosphodiesterase 4 inhibitor, improves patient‐reported outcomes in the treatment of moderate to severe psoriasis: results of two phase III randomized, controlled trials. (10th October 2016) - Thaçi, D.; Kimball, A.; Foley, P.; Poulin, Y.; Levi, E.; Chen, R.; Feldman, S.R.
Abstract: Background: Apremilast, an oral phosphodiesterase 4 inhibitor, has an acceptable safety profile and is effective for treatment of plaque psoriasis and psoriatic arthritis. Objectives: To evaluate the impact of apremilast on health‐related quality of life (HRQOL), general functioning and mental health using patient‐reported outcome (PRO) assessments among patients with moderate to severe plaque psoriasis in the ESTEEM 1 and 2 trials. Methods: A total of 1255 patients were randomized (2 : 1) to apremilast 30 mg BID or placebo for 16 weeks; all received apremilast through Week 32. PRO assessments included the Dermatology Life Quality Index (DLQI), 36‐Item Short‐Form Health Survey version 2 mental/physical component summary scores (SF‐36v2 MCS/PCS), Patient Health Questionnaire‐8 (PHQ‐8), EuroQol‐5D (EQ‐5D) and Work Limitations Questionnaire‐25 (WLQ‐25). Post hoc analyses examined relationships between Psoriasis Area and Severity Index (PASI) scores and PHQ‐8 in the apremilast‐treated population at Week 16. Results: Treatment with apremilast improved all HRQOL PROs at Week 16 (vs. placebo), except the SF‐36v2 PCS, and improvements were sustained through Week 32. Mean DLQI and SF‐36v2 MCS improvements exceeded minimal clinically important differences. Changes at Week 16 in PHQ‐8 and PASI were weakly correlated, and only 35.8% of patients who achieved a ≥75% reduction from baseline in PASI score (PASI‐75) with apremilast treatment also achieved PHQ‐8 scores of 0–4. Conclusions: Apremilast led to improvements in HRQOL PROs vs. placebo in patients with moderate to severe plaque psoriasis.